FAKTOR PENENTU KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA GENERASI MILENIAL DI INDONESIA - Cahyasari, Dyah; Michael, Michael (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to determine the effect of tax knowledge, tax services, and tax digitization on individual taxpayer compliance (WPOP). The population used is the millennial generation who work as private employees. The sample used was 126 employees in the millennial generation category. The sampling technique uses purposive sampling with several criteria, such as: (1) Active private employees in 2019-2023, (2) Has done digital tax reporting, (3) Domiciled in the Greater Jakarta area. The type of data used is primary data, and the collection uses a questionnaire. Partially, the results of the study show that the tax knowledge variable has a negative effect on taxpayer compliance, the tax service variable has a positive effect on taxpayer compliance, while the tax digitization variable has no effect on taxpayer compliance.Keywords: Tax Service, Tax Knowledge, Tax Digitization, Tax Compliance Behavior